Building the evidence base on the agricultural nutrition nexus: Vanuatu - Mackenzie-Reur, Votausi Lucyann; Kulakit Galgal, Keith (Technical Centre for Agricultural and Rural Cooperation, 2018)
A rapid scan on the agriculture and nutrition situation in Vanuatu was undertaken in 2017 to build the evidence base for strengthening the linkage between two important sectors – agriculture and health, for improved food and nutrition outcomes. The food and nutrition situation in Vanuatu has changed over the years as dietary patterns and lifestyles transitioned from a dependence on mostly subsistence living to a more urbanised western lifestyle. Since independence in the early 1980s, food crop production has not significantly increased although the population has almost doubled. In 1983 approximately 0.9 kg of food crops were produced and presumably consumed per capita per day compared to 0.5 kg in 2007. This has resulted in increased dependence on imported foods and the consumption of refined foods that contain higher levels of saturated fats and oils, salt and sugar; less physical activity and increased exposure to other risk factors linked to alcohol intake and smoking. Variation between the food and nutrition situation of rural and urban households and between rural households involved in cash cropping and in subsistence farming, and poor and more affluent urban households have been noted.